2022
DOI: 10.1098/rspa.2021.0607
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in computational fluid dynamics applications for bone tissue engineering

Abstract: Bone injuries or defects that require invasive surgical treatment are a serious clinical issue, particularly when it comes to treatment success and effectiveness. Accordingly, bone tissue engineering (BTE) has been researching the use of computational fluid dynamics (CFD) analysis tools to assist in designing optimal scaffolds that better promote bone growth and repair. This paper aims to offer a comprehensive review of recent studies that use CFD analysis in BTE. The mechanical and fluidic properties of a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…While the use of CFD allows a bioreactor to be optimised for specific tissues, in practice this is not always performed as effectively as it could be. One recent review, for example, highlights that many bioreactors for bone tissue engineering are designed for generic bone tissue engineering, rather than for use modelling specific bones, which could therefore limit their utility due to the wide variability of conditions in different locations [182] .…”
Section: Fluid Flow Parametersmentioning
confidence: 99%
“…While the use of CFD allows a bioreactor to be optimised for specific tissues, in practice this is not always performed as effectively as it could be. One recent review, for example, highlights that many bioreactors for bone tissue engineering are designed for generic bone tissue engineering, rather than for use modelling specific bones, which could therefore limit their utility due to the wide variability of conditions in different locations [182] .…”
Section: Fluid Flow Parametersmentioning
confidence: 99%
“…In tissue engineering (TE) experiments in vitro, cells are usually cultured in a 3D environment, for which porous scaffolds are used for housing the cells [2]. Previous studies have found that scaffold porous geometric characteristics, such as porosity, pore size and pore shape, can influence the internal microfluidic environment, including the WSS on cells within scaffolds [3,4]. Also, according to Refs.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the WSS within scaffold, usually a numerical approach (e.g., based on computational fluid dynamics -CFD model) is needed due to the infeasibility of direct measurement of fluid-induced WSS [4,6]. These CFD models are based on the scaffold geometries from either computer-aided design (CAD) [5,7] or micro-computed tomography (microCT) images [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, computational simulations are normally implemented to reduce the time and cost associated with conceptualizing a new scaffold. For BTE, computational fluid dynamics (CFD) analysis is essential in understanding how changes to a scaffold’s design influence its fluidic properties (such as the WSS) and the underlying cellular processes [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process repeats itself iteratively until a new structure satisfies the objective function. However, in BTE, optimization methods have rarely focused on the fluidic properties of the scaffold [ 14 , 15 , 16 ], instead only consider the scaffold’s mechanical properties (such as their Young’s modulus [ 17 ]; compressive strength [ 18 ] and octahedral shear strain [ 19 , 20 , 21 ]).…”
Section: Introductionmentioning
confidence: 99%